Conferring Higher Prebiotic Fiber Content to Kansas Wheat Lines - Ryan, Nathan; Poland, Jesse; Koo, Dal-Hoe; Wilson, Duane (My University, 2019)
Since the parent translocation lines are homozygous for the barley arm, the first cross will be heterozygous. This heterozygous line will be used to introduce the barley arm to the elite wheat lines in the first backcross. BC1 Hypothesis: The progeny of BC1 will segregate at a l:1 ratio. Half will carry the translocated arm and the other half will not. GISH Hypothesis: All parent lines will be homozygous for the 7H translocation.
Keywords: USDA NIFA 2019-67032-29071